Liberal visions of multiculturalism and majoritarianism - LeVan, A. Carl (Frontiers in Political Science, 2024)
Liberalism advances democratic rights and representation through three principles. First, it seeks to protect individuals from abusive state power. Second, it shares an affinity with the epistemology of the Enlightenment, where an objective world can be discovered and observed. Third, it limits “tyranny of the majority” through civil liberties that counter the weight of public opinion and political rights that enable political competition of ideas. Rapidly evolving demands for recognition in the United States have advanced a broad critique of liberalism, highlighting the boundaries it imposes on representation as well as its limited success protecting rights. This essay traces disenchantment with liberalism to two very different sources: first, many progressives who resent how the jurisprudence of equal opportunity obscures efforts to achieve actual equality reject “anonymity” under the law—removing a core civil rights principle for promoting fairness. Such demands for more explicit rights and representation conflict with the majoritarian model’s application of liberalism, which biases cultural assimilation over multicultural integration. Movements for recognition increasingly challenge both assimilation and the institutional devices of multicultural integration. The other source of tension around recognition comes from the right, where populists have set out to revive nativist ideas of coerced assimilation or outright homogenization through exclusion (ie, non-recognition). Such failures of representation have promoted subjectivist views as a credential for contesting facts. The paper argues for “pluralist solidarity” as a tool for reconciling multiculturalism with new rights and demands for recognition emanating from liberalism’s traditions of individual liberty. This device aims to help separate the quest for recognition and dignity from the subjectivity that contributes to post-truth politics.